Main Categories and Provisions of Linguoculturology. - Fayzieva Sanam (Indonesian Journal of Education Methods Development, 2022)
This paper makes analyses of the main categories and provisions of linguoculturology. On this major both methodological and theoretical basis of the linguoculturology has been analyzed. To conclude with, outcomes and drawbacks of the issue has been pinpointed to get better investigations in further.